You Don't Need a Weatherman : Inigo Manglano-Ovalle ; Stephen Willats ; David Hartt ; Julian Irlinger ; Tris Vonna-Michell ; Mark Lombardi ; Katharina Sieverding (Berlin : Galerie Thomas Schulte, 2018)
Manglano-Ovalle, Inigo ; Willats, Stephen ; Hartt, David ; Irlinger, Julian ; Vonna-Michell, Tris ; Lombardi, Mark ; Sierverding, Katharina
The starting point for the artists featured in You Don’t Need a Weatherman are investigations aimed at revealing social dynamics, economic systems, and political relations within an increasingly complex world of virtual representation, infinite sources of information, and invisible data flows. They do this through various artistic approaches organizing readily available information and footage creating new narratives, systems, and structures.(from publisher)
You Don't Need a Weatherman, Galerie Thomas Schulte, Berlin, 10 december to 28 january 2017
boek